Limited impact of adolescent meningococcal ACWY vaccination on Neisseria meningitides serogroup W carriage in university students - Oldfield, Neil J.; Green, Luke R.; Parkhill, Julian; Bayliss, Christopher D.; Turner, David P.J. (Oxford University Press, 2018)
Background